Student-based evaluation on the pedagogical, professional, social, and personal competencies of ESP teachers - Luluk Iswati (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2026)
This research examines the pedagogical, professional, personal, and social competencies of English for Specific Purposes (ESP) teachers teaching Business English in the context of Outcome-Based Education (OBE). It aims to evaluate students’ perceptions of teachers’ competencies and to identify areas of requiring improvement to support effective leanring outcomes. A mixed-method approach was employed, involving a survey to 310 undergraduate students enrolled in Business English course. The questionnaire consisted of Likert-scale items to capture quantitative data and open-ended questions to elicit qualitative insights into students’ learning experiences. Quantitative data were analyzed descriptively to identify trends and mean scores across competency domains, while qualitative responses were analyzed through thematic analysis to uncover recurring patterns and critical issues. The results show that generally teachers’ pedagogical, personal, and social competencies are very good, but the professional competencies received the lowest score because the materials suitability with students’ ability is perceived low and online classes were dominant. Qualitative data further revealed teachers’ monotonous teaching methods, lack of interactiveness, and limited communication responses. These findings emphasize the need to increase teachers’ pedagogical and professional competencies through ESP training, needs analysis, materials development, and interactive teaching strategies to ensure effective learning in accordance with the demands of OBE Curriculum.